2020
DOI: 10.7759/cureus.8696
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Surgeon’s Experience as a Risk Factor for Post-Esophagectomy Chylothorax on a Four-Year Cohort

Abstract: Background: Chylothorax (CHT) is a known post-operative complication after esophageal surgery with vaguely defined risk factors. Methods: This is a retrospective chart review of 70 consecutive patients with operable cancer over a period of four years (January 2013 to December 2016). Ivor Lewis and McKeown interventions were performed. Thoracic duct is identified and ligated routinely. Factors related to the patient, the tumor, and the operating surgeon were analyzed. Results: Incidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Another controversial issue is that the incidence of this complication has not been determined accurately and that there are major differences between various reports in this regard (8,12,13,15,16). There is considerable difference between studies regarding the reports of post-esophagectomy chylothorax, with low incidence in our patients but higher prevalence reported in other studies (2,17).…”
Section: Risk Factorsmentioning
confidence: 73%
“…Another controversial issue is that the incidence of this complication has not been determined accurately and that there are major differences between various reports in this regard (8,12,13,15,16). There is considerable difference between studies regarding the reports of post-esophagectomy chylothorax, with low incidence in our patients but higher prevalence reported in other studies (2,17).…”
Section: Risk Factorsmentioning
confidence: 73%
“…Following propensity score matching, multivariable logistic regression models adjusted for covariates chosen a priori to control for patient morbidity and proposed risk factors of chylothorax following esophagectomy from prior studies. 6 , 7 , 8 In the matched cohort, the association of underweight status with chylothorax or other postoperative complications, after adjusting for Charlson Comorbidity Index, history of chemotherapy or radiation therapy, minimally invasive approach, and resection of thoracic lymphatics was assessed ( Table 2 ). Patients who were underweight were estimated to have 2.06 times the odds for chylothorax (95% CI, 1.07-4.25, P = .035) in the multivariable analysis.…”
Section: Resultsmentioning
confidence: 99%
“… 3 , 4 , 7 Previous studies have shown mixed associations between chylothorax and preoperative chemotherapy or chemoradiation therapy. 4 , 6 , 8 Therefore, our study controlled for preoperative chemotherapy and/or radiation therapy in the matched analysis and multivariable logistic regression models. In the multivariable analysis, underweight status remained a significant risk factor for development of chylothorax.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations